Singapore negotiating state and society, 1965-2015 - Lim, Jason 1971-; Lee, Terence 1972- (London Routledge Taylor & Francis Group, 2016)
"Critically reflects on 50 years of independence. Contributors interrogate a selected range of topics on Singapore's history, culture and society--including the constitution, education, religion and race--and thereby facilitate a better understanding of Singapore's shared national past. Central to this book is an examination of how Singaporeans have learnt to adapt and change in the face of policies introduced by the PAP government since independence in 1965. All chapters begin their histories from that point in time, and each contribution focuses either on an area that has been neglected in Singapore's modern history or offers new perspectives on the past. Using a multi-disciplinary approach, this book presents an independent and critical take on Singapore's post-1965 history".
Negotiating state and society in Singapore : rethinking historical narratives / Jason Lim and Terence Lee -- Constraint or restraint? : Singapore's constitution at 50 / Jack Tsen-Ta Lee -- The political opposition and its protracted journey towards a two-party system / Jason Lim -- Race rules in Singapore / Geetha Reddy -- The changing landscape of politics and language use in Singaporean theatre : towards a multilingual praxis / Wah Guan Lim -- The church and the state in Singapore / Terence Chong -- Hinduisms and post-independent Singapore / Bittandra Chand Somaiah -- The deity proposes, the state disposes : the vicissitudes of a Chinese temple in post-1965 Singapore / Keng We Koh -- Defending the dharma : Buddhist activism in a global city-state / Jack Meng-Tat Chia -- The role of modern Islam in Singapore / Rizwana Abdul Azeez -- Arts, aspiration and anxieties : cultural policy in Singapore / Terence Lee -- Rock 'n roll & the restringing and resounding of the Singapore story / Kai Khiun Liew -- Citizenship education : 50 years of constructing and promoting national identity in schools / Christine Han.
Includes bibliographical references (pages 216-239) and index.
Keywords: Singapore -- History -- 1965-1990.; Singapore -- History -- 1990-.; Singapore -- Civilization